WITCHES’S RITES THAT OCCURRED IN TV SERIES: CHILLING ADVENTURES OF SABRINA - Yudha Nur Widiananta; Bunyamin Faisal; Yoga Sudarisman (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
Magic is a concept used to describe the power that comes from supernatural powers to make impossible things happen, make people disappear or even control natural events. As time goes by, magic has developed to be the theme in literature. One of theme is TV series: Chilling Adventures of Sabrina. The writer focuses the analysis on the rites that occur in this series. The writer used Marcell Mauss’s theory that was written in his book A General Theory of Magic. From his book, it can be seen that they are several things that the witch must prepare when they want to do the rites such as time, place and many more. A descriptive qualitative by Creswell was used in this study. The result from this study is when the witchcraft wanted to do the rite, they must prepare the time, place, materials and incantation. The different rite has a different purpose and also different things that they must prepare.